State-level autonomy in the era of accountability: A comparative analysis of Virginia and Nebraska education policy through No Child Left Behind - Ryan Richard Ruff (Arizona State University, 2019)
Following the 1983 A Nation at Risk report and culminating in No Child Left Behind (NCLB), states designed and implemented accountability policies to evaluate student achievement. External assessments of these policies identified substantial variability in the level of stakes associated with each system. This paper presents a comparative analysis of accountability policy prior to and during implementation of NCLB. Using the Virginia Standards of Learning and the Nebraska School-based Teacher-led Assessment and Reporting System, it explores the role of the historical and political context in shaping assessment policy through the lenses of the processes, conditions, and consequences of the policy process. It concludes that the influence of Nebraskan historical culture embedded the role of local action in the design and interpretation of accountability policy, which when combined with the collaborative efforts of the board of education, legislature, and executive branch, resulted in an atypical assessment model involving actors across the policy process. The Virginia experience was characterized by a strong political identity of centralization, yielding a top-down accountability system that constrained resources and opportunities for transforming policy at local levels. Findings demonstrate how comparable policy intentions for accountability are transformed due to existing state-level conditions and local policy culture.